Assessment of Diagnosed Temporomandibular Disorders and Orofacial Pain Conditions by Predoctoral Dental Students: A Pilot Study. Issue 12 (1st December 2016) - Adibi, Shawn S.; Kookal, Krishna Kumar; Fishbeck, Nichole M.; Thompson, Chris R.; Walji, Muhammad F.
Abstract : Temporomandibular disorders and orofacial pain (TMD/OFP) conditions are challenging to diagnose for predoctoral dental students due to the multifactorial etiology, complexity, and controversial issues surrounding these conditions. The aim of this study was to determine if patients in the clinic of one U.S. dental school reported existing signs and symptoms of TMD/OFP, whether the dental students diagnosed the condition based on the reported signs and symptoms, and if the condition was then treated. The study was based on a retrospective analysis of electronic health record data over a three‐year period. The results showed that, during the study period, 21, 352 patients were treated by student providers. Of those patients, 5.33% reported signs or symptoms associated with TMD/OFP; 5.99% received a TMD/OFP diagnosis; and 0.26% received at least one form of TMD/OFP treatment that had either a diagnosis or signs/symptoms of TMD/OFP. In addition, a small percentage (0.24%) of patients with no documented diagnosis received some sort of TMD/OFP‐related treatment. A randomly selected sample of 90 patient charts found that no diagnoses of TMD/OFP were recorded in any of them. The results suggested that students had only marginally diagnosed the problems. Training for students including comprehensive didactic courses and clinical experiences to gain knowledge, context, and skill may be required to ensure they reach the required level of competence and prepare them to face the diagnostic challenges of TMD/OFP after graduation.